FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB) DI DESA KOTO TALUK KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2011-2014 - Fernandi, Yuanda Kurnia; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Property tax revenues are essential to the development of facilities and infrastructure in the village of Koto Taluk sub-districts Kuantan Tengah district Kuantan Singingi. The state can provide the facilities and infrastructure for the public use of tax funds. Payment of taxes we do to improve the living standards of future generation. The nation’s progress is determined by the consciousness of the people’s to understand and pay taxes properly.The purpose of this research was to determine the factors that affect the low property tax revenues in the village Koto Taluk sub-districts Kuantan Tengah district Kuantan Singingi in years 2012-2014. Types of research is a qualitative research (research that cling to the naturalistic paradigm and phenomenology), the informant many as 14 people.The results of research, affecting the low property tax revenues in the village Koto Taluk sub-districts Kuantan Tengah district Kuantan Singingi in years 2011-2014. Influenced by internal and external factors. External factors affecting low property tax consists of, weak legal system and bureaucracy, weak capacity of government officials and budget, weak public administration and system control/supervision can’t be carried properly. While external factors affecting the low property tax consists of intellectual development level of public education and lack of public awareness of the property tax.Keywords: Low Acceptance Factors, Property Tax